A MIXED PROBLEM FOR THE FOURTH ORDER DEGENERATE ORDINARY DIFFERENTIAL EQUATION - Yousefi, Esmail (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
A mixed problem for the equation $ Lu\equiv (t^{α}u'')''+α u=f $ (1)is considered. Firstly, the weighted Sobolev spaces $W_α^2,~ W_{α}^2(0),~W_{α}^2(b)$ and the generalized solution to equation (1) are defined. Next, the existence and uniqueness of the generalized solution for the mixed problem is studied, as well as the description of the spectrum of corresponding operator is given.
Keywords: mixed problem; weighted Sobolev spaces; generalized solution; spectrum of linear operators